Effects of rule changes on game-related statistics in men`s water polo matches - Madera, J.; Tella, V.; Saavedra, J. M. (Sports, 2017)
The aim of this study was to investigate the effects of rule changes on game-related statistics in men`s water polo matches. A total of 856 men`s matches played in all Olympic Games and World Championship since 1936 was analysed. The game-related statistics considered were: total goals, winners` goals, losers` goals, goals per minute, goals difference, relationship difference goals and total goals, and relationship difference goals and winners` goals. The rule changes were grouped by structural (game and period) and functional changes (possession time, exclusion time, timing, minimum distance to take a direct shot). Differences between rule changes were determined using a one-way ANOVA. In general, the changes in water polo rules were shown to have an effect on the final result of the matches. There were differences in each rule change of duration (increased total goals and winners` goals), period (increased total goals and winners` goals), possession time (increased losers` goals), timing (increased total, winners`, losers`, and decreased % goals and total goals) and fouls (increased total goals and losers` goals). The analysis in game-related statistics through the rule changes could be used to evaluate their effects and/or justify future modifications